Suicide and Suicide-Related Behaviors: A Multi-Perspective Explanation and Implications for Suicide Prevention Strategy in Vietnam - Dinh Phuong Linh (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Suicide and suicide-related behaviors have been widely recognized as a serious public health issue and have become a popular topic among the scholar community. Thus, in Vietnam, the exact statistics of suicide have not yet been unveiled and there lacks a comprehensive system to record cause-of-death in the country. This article discusses the controversy around terminology in suicidology and seeks to explain the act of suicide under a multi-disciplinary prism. International experiences on suicide prevention are also analyzed, which helps to propose some implications for the suicide prevention strategy in the country. Received 8th September 2017; Revised 1st October 2018; Accepted 10th October 2018